Pengaruh Terapi Playdough terhadap Peningkatan Perkembangan Motorik Halus Anak Usia Prasekolah di TK PGRI 21 Kota Semarang - Erni Suprapti; Yuni Astuti (Jurnal Multidisiplin Indonesia, 2026)
Fine motor skills are one aspect of development in preschool children to support their independence and readiness to learn. Children’s fine motor development can be assessed using the KPSP (Pre-Screening Questionnaire for Development) which is an early detection instrument in the development of children aged 0 to 6 years. Fine motor development needs to be stimulated so that children can develop optimally. One stimulation method that can be used is by playing playdough, which is an activity of forming soft dough using hands that involves small muscle coordination and finger movement control. The purpose of this study was to determine the effect of playdough play therapy on the development of fine motor skills in preschool children. The design of this study was to use a Quasy experiment with one group pre-test-post-test design. The number of samples was 17 respondents with a purposive sampling model. The results of this study indicate that there is an effect of playdough play therapy on improving fine motor development in preschool children with a p-value of 0.001. The conclusion of this study is that there is an increase in fine motor development after the application of playdough play therapy in preschool children. Parents are advised to do this playdough play therapy at home to be able to further optimize their child’s development, especially fine motor development.